Optimalisasi Sanitasi Ruang Produksi Usaha Kecil Menengah Kue Semprit Menggunakan Exhaust System dan Mesin Extractor - Chandra Sundaygara; Maris Kurniawati; Chandra Wahyu Hidayat (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
One of the Small and Medium Enterprises (UKM) in Sukun District is Semprit Cake UKM. UKM The problems faced by partners are problems in the field of production. The production problems experienced by partners include the process of producing semprit cakes takes a long time because partners still use manual methods starting from production to squeezing coconut milk until it becomes a cake, and sanitation of the production room that does not pay attention to air circulation, such as the use of a wood-burning stove that is not equipped with a smoke exhaust pipe, so that it can endanger the health of partners and employees. Therefore, the purpose of carrying out this Community Service is to provide solutions to solve the problems experienced by Kue Semprit UKM Partners in the field of production through technology transfer using an exhaust system and extractor machine. The positive impacts obtained after carrying out this community service activity include the sanitation of the semprit cake production room becoming cleaner and cooler because air circulation is smoother, coconut milk production takes less time, partners have a good understanding of the importance of room sanitation, and partners have the ability to operate and maintain coconut milk extractor machines and exhaust systems.